Analysis of Factors Influencing Customer Satisfaction and Its Impact on Mobile Banking Customer Loyalty - Felix, Modefica Adelina; Sugiat, Maria Apsari (International Journal of Management and Digital Business, 2024)
Various studies have tested customer satisfaction factors in mobile banking services that have a direct influence on loyalty. The main objective of this study is to determine customer satisfaction factors in Mobile Banking Service Quality (MBSQ) services that have a direct and indirect influence on customer loyalty. This study uses a quantitative method approach, the research type design uses descriptive and verification, in testing the research model using the Structural Equation Model Partial Least Square (SEM-PLS) approach. The results of the study show that expense, security, responsiveness, relative advantage, and convenience factors have a direct effect on customer satisfaction, the findings of this study confirm that costs have an indirect effect on customer loyalty through customer satisfaction. Customer satisfaction becomes a process or helps transmit service quality to loyalty in the banking industry. The benefits of this research provide benefits both theoretically and in managerial practice, this research can enrich knowledge related to digital-based banking service marketing strategies, so that it has an impact on customer satisfaction and loyalty, and can increase sustainable competitiveness for the company.